2017
DOI: 10.1039/c7cp00567a
|View full text |Cite
|
Sign up to set email alerts
|

Plasma treatment effect on polymer buried interfacial structure and property

Abstract: Adhesion is important in many industrial applications including those in the microelectronics industry. Flip-chip assemblies commonly utilize epoxy underfills to promote reliability and the buried interfacial structure of underfills is crucial to device lifetime. Poor adhesion at this interface can cause premature device failure. One method to increase adhesion strength is to plasma treat the substrate attached to underfills, however, the mechanism of this increase in adhesion strength has not been thoroughly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“…Sum frequency generation (SFG) vibrational spectroscopy, a second-order nonlinear optical technique, can noninvasively probe any surface or nonopaque interface to acquire molecular-level structural information such as chemical species, molecular orientation, orientation distribution, interfacial interaction, and so forth. To date, extensive studies have been reported on probing the molecular-level structures and dynamics at the polymer surfaces and interfaces using SFG spectroscopy. For instance, SFG was used to detect the structural characteristics and restructuring behaviors of polymer surfaces. SFG has been applied to investigate the interfacial structures of epoxy adhesives with respect to composite materials. ,, In addition, SFG has also been utilized to probe functional interfaces between silane-based adhesive promoters and model polymers, which play an important role in enhancing the interfacial adhesion and mitigating the hydrothermal aging. ,,,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy, a second-order nonlinear optical technique, can noninvasively probe any surface or nonopaque interface to acquire molecular-level structural information such as chemical species, molecular orientation, orientation distribution, interfacial interaction, and so forth. To date, extensive studies have been reported on probing the molecular-level structures and dynamics at the polymer surfaces and interfaces using SFG spectroscopy. For instance, SFG was used to detect the structural characteristics and restructuring behaviors of polymer surfaces. SFG has been applied to investigate the interfacial structures of epoxy adhesives with respect to composite materials. ,, In addition, SFG has also been utilized to probe functional interfaces between silane-based adhesive promoters and model polymers, which play an important role in enhancing the interfacial adhesion and mitigating the hydrothermal aging. ,,,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…However, these techniques lack general monolayer surface and interfacial selectivity and sensitivity. Over the past three decades, sum frequency generation (SFG) vibrational spectroscopy has proven to be a powerful technique to directly and nondestructively study polymer surfaces/interfaces due to its inherently surface/interfacial specific selectivity and sensitivity, and its capability to provide molecular level structural information in situ. SFG has been used extensively to characterize molecular structures at buried polymer/solid or polymer/liquid interfaces. ,, In this study, we push the boundaries of SFG to systematically analyze chemical reactions at the buried polymer/polymer interface of nylon and maleic-anhydride grafted polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information on the buried interfaces between the polymer thin films in the multilayer samples has seldom been investigated nondestructively at the molecular level due to the lack of appropriate analytical tools to probe this information. Sum frequency generation (SFG) vibrational spectroscopy is a second-order nonlinear optical technique and a powerful nondestructive, in situ tool to study the molecular structure of the buried interfacial structures, with sub-monolayer interface specificity. SFG has been extensively applied to study many buried solid/solid interfaces involving a variety of polymers. Recently, we have reported molecular orientation information, especially for methylene groups, at buried interfaces of nylon and functionalized polyolefin materials . In this study, we expand this to investigate the molecular structure of the nylon/MAH-grafted polyethylene buried interface, focusing on the polar CO groups of MAH-grafted polyethylene at buried CaF 2 and nylon interfaces in situ.…”
Section: Introductionmentioning
confidence: 99%